Nuclear factor kappa B–mediated CD47 up‐regulation promotes sorafenib resistance and its blockade synergizes the effect of sorafenib in hepatocellular carcinoma in mice. Issue 2 (3rd June 2015) - Lo, Jessica; Lau, Eunice Yuen Ting; Ching, Rachel Hiu Ha; Cheng, Bowie Yik Ling; Ma, Mark Kin Fai; Ng, Irene Oi Lin; Lee, Terence Kin Wah
<x xml:space="preserve">Abstract</x> Sorafenib is a new standard treatment for patients with advanced hepatocellular carcinoma (HCC). However, the survival benefit of this treatment is modest, partly owing to drug resistance. Recent evidence has demonstrated the existence of tumor‐initiating cells (T‐ICs) as the culprit for treatment resistance. To examine whether sorafenib resistance was a result of the presence of liver T‐ICs, we developed sorafenib‐resistant HCC cells both in vitro and in vivo through continuous exposure to sorafenib. Using these models, we found that sorafenib‐resistant clones demonstrated enhanced T‐IC properties, including tumorigenicity, self‐renewal, and invasiveness. In addition, several T‐IC markers were found to be up‐regulated, among which CD47 was found to be most significant. Using chromatin immunoprecipitation assays and expression analyses, CD47 expression was found to be regulated by nuclear factor kappa B (NF‐κB) through a specific response element in the promoter of CD47, and the site occupancy and expression were increased and decreased upon stimulation and inhibition of NF‐κB, respectively. Consistently, NF‐κB was activated in sorafenib‐resistant HCC cells, and this finding was confirmed in clinical HCC samples, which showed a positive correlation between NF‐κB and CD47 expression. Functional characterization of CD47 in sorafenib‐resistant HCC cells was evaluated using a lentivirus‐based knockdown approach and showed increased sensitization to sorafenib upon CD47 knockdown. Furthermore, blockade of CD47 using anti‐CD47 antibody (Ab) showed a similar effect. Using a patient‐derived HCC xenograft mouse model, we found that anti‐CD47 Ab (500 μg/mouse) in combination with sorafenib (100 mg/kg, orally) exerted synergistic effects on tumor suppression, as compared with sorafenib and anti‐CD47 Ab alone. Conclusions: NF‐κB‐mediated CD47 up‐regulation promotes sorafenib resistance, and targeting CD47 in combination with sorafenib is an attractive therapeutic regimen for the treatment of HCC patients. (Hepatology 2015;62:534–545